(3MeGjI GdeSJgdc aj Gdabg GdGbJUGOj GdGSdGej(B-(3OQGSI ebGQfI(B-s - (3ehab eMeO(B, (3YHOgs ((3YeGf(B:s (3GdeLOdGhj(B,s, 2002)
(3GdGSJgdGc,GdGfJGL,GdhSGFd GdJj GJHYgG GdGSdGe dMeGjI GdeSJgdcs
(3GdeQGLY U(B.339s
Keywords: (3GdeSJgdchfs; (3MeGjI GdeSJgdcs